Academic Stress and Depression in Adolescents from a High School Post COVID- 9 Pandemic - Criollo, Katherine; Valle , Isabel (Revista Ecos de la Academia, 2024)
The objective of this research is to compare academic stress and depression in adolescents from an educational unit in the post-COVID-19 pandemic. A quantitative methodology was used, of a comparative descriptive type, with a non-experimental cross-sectional design. The participants were 90 students to whom the sociodemographic sheet, the SISCO-V21 test and the Beck Depression Inventory-II were applied. The results indicated that both men (69.4%) and women (75.6%) had moderate academic stress, and women obtained minimal and moderate depression in 30.6% respectively, unlike men who presented depression. severe (39%). The comparative analysis indicated that there are no statistically significant differences in both academic stress (t = 1.290; p = 0.201) and depression (t = -1.889; p = 0.062) depending on sex, but there are in the stressors dimension of the variable. of academic stress (t=2.276, p= .025) with higher levels in women compared to men.